1973
DOI: 10.1007/bf01250504
|View full text |Cite
|
Sign up to set email alerts
|

B-type oncornaviruses isolated from continuous human cancer cell Lines

Abstract: SummaryEleven lines and sublines of larynx carcinoma (HEp-2), cervical cancer (IteLa) and dedifferentiated astrocytoma (DAPT) cells were examined and viruses were isolated from eight lines. Electronmicroscopic, biophysical and biochemical examinations of the viruses showed that they belong to the B-type oneornaviruses. The virions had a size of 100 to 150 nm, they banded at densities of 1.16 to 1.17 g/ ml in sucrose gradients and t~NA from the virions contained 60--70 S component. The reproduction of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In many published studies other evidence (such as from electron microscopy) has supported the viral nature of the labelled particles, but one recent report (Narayan and Rounds, 1973) suggested that uridine-labelling in HeLa cells was associated with small (10-12 nm) ring-shaped particles. In contrast, Bykovsky et al (1973) have reported the presence in HeLa cells of a typical B-type oncornavirus. Small ring-shaped particles were present in the fluids from the melanoma cell lines but evidence from the filtration experiments strongly suggested that the uridine-labelled melanoma particles being investigated were much larger.…”
Section: Discussionmentioning
confidence: 81%
“…In many published studies other evidence (such as from electron microscopy) has supported the viral nature of the labelled particles, but one recent report (Narayan and Rounds, 1973) suggested that uridine-labelling in HeLa cells was associated with small (10-12 nm) ring-shaped particles. In contrast, Bykovsky et al (1973) have reported the presence in HeLa cells of a typical B-type oncornavirus. Small ring-shaped particles were present in the fluids from the melanoma cell lines but evidence from the filtration experiments strongly suggested that the uridine-labelled melanoma particles being investigated were much larger.…”
Section: Discussionmentioning
confidence: 81%
“…The occurrence of reverse transcriptase activity was not apparently related to the presence of the 'blebs' in 720301 and 710025 cells, but it is nevertheless of interest in view of the recent demonstration by Bykovsky, Miller, Yershov, Ilyin, and Zhdanov (1973) of similar activity in human cancer cell lines. In our case, however, we were unable to find morphological evidence of B-type particles in the cells.…”
Section: Discussionmentioning
confidence: 92%
“…This system attracted our attention again after it has been shown that some clones of ttEp2 cells contained an oncornavirus (7). In the course of this study we have found that the cells chronically infected with the virus contain the viral genome transcribed into DNA and integrated into the cell nucleus, allowing therefore transfection of virus to a sensitive cell system.…”
Section: Introductionmentioning
confidence: 99%